Urgency Of Waste Import Regulations For Communities In East Java - Purwanto, Aldira Mara Ditta Caesar; Aryani, Maria Indira (VJJ, 2022)
Currently, waste management is a big problem, not only in Indonesia but also throughout the world. Especially after the People's Republic of China (PRC) changed its solid waste import policy on July 18, 2017. The issuance of the National Sword policy aims to limit and tighten imports of plastic waste. The impact of the PRC's policy change is an increase in the flow of waste imports to Indonesia, thus placing Indonesia as a "Plastic Waste Emergency" country. To overcome this problem, Indonesia already has several regulations and laws related to waste imports. The application of waste import rules that are not strict causes losses for local communities in East Java and Surabaya. This study then aims to find out that the import of waste has an impact not only on the environment but also on the political economy and the efforts made by the local government to overcome it. This study uses social research methods based on a qualitative descriptive approach. This study also uses field research methods to obtain data directly from the research object area. There are four data collection techniques, namely observation, questionnaires, Focus Group Discussion (FGD), and documentation. The research subjects chosen were the people of Bangun Village, Mojokerto, and several regional (local) policy-making bodies in Surabaya and East Java. This study will also use a non-random sampling technique, with the selection of samples using purposive sampling. Field data collection will be carried out using interviews conducted directly with the informants using interview guidelines.